Benign spasms of infancy: a mimicker of infantile epileptic disorders. Issue 6 (17th January 2020) - Ghossein, Jamie; Pohl, Daniela
ABSTRACT: Benign spasms of infancy (BSI), previously described as benign non‐epileptic infantile spasms or benign myoclonus of early infancy, are non‐epileptic movements manifesting during the first year of life and spontaneously resolving in the second year of life. BSI are characterized by spasms typically lasting 1–2 seconds, involving, to varying degrees, the head, neck, trunk, shoulders and upper extremities. Ictal and interictal EEG recordings are normal. BSI are not associated with developmental regression and do not require treatment. Distinction between BSI and infantile epileptic disorders, such as epileptic spasms or myoclonic epilepsy of infancy, can be challenging given the clinical similarities. Moreover, interictal EEGs can be normal in all conditions. Epileptic spasms and myoclonic epilepsy require timely treatment to improve neurodevelopmental outcomes. We describe a six‐month‐old infant presenting with spasm‐like movements. His paroxysms as well as a positive family history for epileptic spasms were in keeping with a likely diagnosis of West syndrome. Surprisingly, ictal video‐EEG did not reveal epileptiform activity, and suggested a diagnosis of BSI. We emphasize that ictal video‐EEG is the gold standard for classification of infantile paroxysms as epileptic or non‐epileptic, thereby avoiding over‐treatment for BSI and facilitating timely targeted treatment of infantile epilepsies. [ Published with video sequences ]